A comparison of the stress corrosion cracking susceptibility of commercially pure titanium grade 4 in Ringer's solution and in distilled water: A fracture mechanics approach. Issue 1 (13th July 2013) - Roach, Michael D.; Williamson, R. Scott; Thomas, Joseph A.; Griggs, Jason A.; Zardiackas, Lyle D.
Abstract From the results of laboratory investigations reported in the literature, it has been suggested that stress corrosion cracking (SCC) mechanisms may contribute to early failures in titanium alloys that have elevated oxygen concentrations. However, the susceptibility of titanium alloys to SCC in physiological environments remains unclear. In this study, a fracture mechanics approach was used to examine the SCC susceptibility of CP titanium grade 4 in Ringer's solution and distilled de‐ionized (DI) water, at 37°C. The study duration was 26 weeks, simulating the non‐union declaration of a plated fracture. Four wedge loads were used corresponding to 86–95% of the alloy's ligament yield load. The longest cracks were measured to be 0.18 mm and 0.10 mm in Ringer's solution and DI water, respectively. SEM analysis revealed no evidence of extensive fluting and quasi‐cleavage fracture features which, in literature reports, were attributed to SCC. We thus postulate that the Ringer's solution accelerated the wedge‐loaded crack growth without producing the critical stresses needed to change the fracture mechanism. Regression analysis of the crack length results led to a significant best‐fit relationship between crack growth velocity (independent variable) and test electrolyte, initial wedge load, and time of immersion of specimen in electrolyte (dependent variables). © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 73–79, 2014.